Sebuah ANALISIS ASPEK DINAMIKA POPULASI IKAN CAKALANG (KATSUWONUS PELAMIS) YANG DIDARATKAN DI PELABUHAN PERIKANAN PANTAI (PPP) PONDOKDADAP SENDANGBIRU KABUPATEN MALANG, JAWA TIMUR: ANALISIS ASPEK DINAMIKA POPULASI IKAN CAKALANG (KATSUWONUS PELAMIS) - Nugraeni, Bidari Rahma (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2023)
Skipjack tuna (Katsuwonus pelamis) is one of the largest export commodities in IndonesiaPondokdadap Beach Fishing Port. Analysis of aspects of population dynamicsis an important step taken to determine the condition of skipjack fish stockssustainability in the waters of the Indian Ocean. Long data collection is done at TPISendang Biru during March - July 2022 with a total sample of 3,875 individuals.The length frequency distribution data (cm) were analyzed using the FAO-ICLARM Stock programAssessment Tools (FISAT) to estimate parameters of growth, mortality, exploitation,recruitment, yr/br and stock prediction. The results of the population parameter analysis are as follows, lengthasymptote (L∞) 68.39 cm; growth rate coefficient (K) 0.31 per year and theoretical age (t0) -0.42 years. Total mortality value (Z) 4.27 per year; natural mortality (M) 0.66 per year andfishing mortality (F) 3.61 per year. Exploitation rate (E) 0.85 per year incloverexploited. The peak of recruitment occurred in June with a value of 16.53%. yr analysisget a value of 0.019 per year and br 0.054 per year. Maximum potential estimated valuesustainable (MSY) of 46622 tons with an optimum fishing effort (FMSY) value of539 trips. The exploitation rate has a value of 457% and the utilization rate is 1%.